The Employment Problem in Latin America: Perceptions and Stylized Facts - Eduardo Lora; Gustavo Márquez (Inter-American Development Bank, Office of the Chief Economist, 1998)
This article, which serves as an introduction to a group of studies prepared by the IDB Office of the Chief Economist, presents the perceptions of Latin American citizens and employers concerning the employment problem. It compares them to the conditions in the labor markets of the region.
Keywords: 330; Erwerbstätigkeit; Arbeitsmarkt; Arbeitslosigkeit; Lateinamerika